Marine Mammal Species Confirmed from Philippine Waters - Leatherwood, Stephen; Dolar, Maria Louella L.; Wood, Cola J.; Aengones, Lemuel V.; Hille, Cynthia L. (Silliman Journal, 2024)
In 1990, the authors began compiling information,(from strandings, interviews, trained observers aboard fishing vessels, unpublished sources, examination of specimens taken in fisheries, and surveys) on marine mammal presence, relative abundance, and involvement in fisheries in Philippine waters. _ Through September 1992, the Philippine marine mammal fauna had been confirmed to include 17 species. At least those indicated are involved in directed fisheries (+) or are taken incidental to gillnetting or seining operations (*): Risso’s (+*), bottlenose (+*), rough-toothed (*), pantropical spotted (+*), long-snouted spinner (+*), and Fraser’s (+*) dolphins, melon-headed (+*), pygmy-killer, short-finned pilot (+*), Blainville’s beaked (+), sperm (+), pygmy sperm (+), dwarf-sperm, humpback (+), minke and Bryde’s (+) whales, and dugongs (+*). Hight other species for which yet uncon- firmed reports exist are: striped, common and Indo-Pacific humpbacked dolphins, and blue, bottlenose, goosebeaked, killer, and false killer whales. There is evidence that incidental takes in fishing operations have given rise to directed fisheries for small cetaceans as human populations have burgeoned and traditionally harvested marine species have declined.